Modification of Papercraft Play Therapy Combined with Music Therapy on the Social- Emotional Development of Preschool Children - Retty Nirmala Santiasari; Budi Artini; Meilan Meilan; Grayvhany Zhyeriel Chrizhara Banu (Universitas Nahdlatul Ulama Surabaya, 2026)
The prevalence of emotional development disorders in children is still quite high. Thus, stimulating children's social-emotional development is critical. This paper evaluates whether children's social-emotional development improves after receiving papercraft play therapy combined with music therapy. This study used a quasi-experimental pretest- posttest design. The population was preschool children (5–6 years old) at TK Kristen Dharma Mulya. The sample was 60 children selected using a purposive sampling technique. It was divided into three groups: two intervention groups and one control group—Group A: papercraft play therapy; Group B: papercraft play therapy combined with music therapy; and Group C: routine play activities. The research instruments were the Emotion Regulation Checklist (ERC). Statistical analysis used ANOVA, with α≤0.05. In Group A, the social-emotional development of children in the pre-test was in the poor category at 70%. Meanwhile, in the post-test, it improved to the good category at 55%. In Group B, social-emotional development in the pre-test was in the poor category at 55%. In the post-test, it increased to the adequate category at 45%. In Group C, 65% of children were in the poor category at the pre-test, and 50% remained in the poor category at the post-test. ANOVA analysis showed significant differences among the three groups (p=0.001). Post hoc tests indicated that Group B showed greater improvement in children's social-emotional development than the other groups. In conclusion, papercraft therapy combined with music therapy is more effective for social-emotional development in preschool children than papercraft therapy alone or routine play activities.